Deteksi Johne’s Disease pada Sapi Potong di Kabupaten Kebumen Berdasarkan Uji Elisa - Iip Zuliana Rachmawati; Widagdo Sri Nugroho; Rahmat Setya Adji (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
Kebumen Regency have been set as the source of the beef cattle breeds by the Ministry of Agriculture of the Republic of Indonesia. As the parent stock of beef cattle, these should be free from any infectious disease. Base on Balai Besar Veterinary Wates survey at 2015, some beef cattle in some districts at Kebumen indicated Johne's Disease. This research was carried out with the epidemiologic approach to detect Johne's Disease. About 173 serum specimens were taken from 173 heads of cows who have clinical symptoms of Johne's Disease. Sera were analyzed by ELISA. Base on ELISA result, 38 from 173 serum were seropositive. These cows sample come from local ancestor and there were not Johne’s disease vaccination program in Kebumen. This research proved that Johne's Disease have occurred in this populations which dedicated for parent stock of beef cattle in the District of Kebumen. Disease control program for Johne’s disease should be undertaken in this area to prevent the disease transmition.